Factors Affecting User Satisfaction with Online Food Delivery Service Applications in Indonesia (Gofood, Grabfood, Dan Shopeefood) - Aurelia Salsabila Putri; Roni Zakaria Zakaria; Yuniaristanto Yuniaristanto Yuniaristanto (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2022)
The growth and development of food delivery service applications in Indonesia has occurred very rapidly in the last 4 years. Digitization in the food and beverage sector in Indonesia is supported by the growth and development of food delivery service applications, namely Gofood and Grabfood, which focus on service providers selling, ordering and delivering food and beverages from places of sale to consumers. Gofood and Grabfood are currently the two largest food delivery application services in Indonesia with quite fierce competition between the two. In the midst of the progress of these two food delivery services, a new phenomenon has emerged where there are new players entering the competition in the food delivery service industry in Indonesia, namely from one of the largest e-commerce platforms in Indonesia and Southeast Asia called Shopee, namely Shopee Food. The emergence of ShopeeFood makes the competition in the food delivery service application industry increasingly tight in Indonesia. Application users have more choices to use the application and choose to be satisfied or dissatisfied with the application for the services provided. Among this fairly tight competition, therefore, identification is needed to find out what factors can increase user satisfaction in Indonesia with food delivery service applications.